Habitat suitability and distribution potential of Liberibacter species ("Candidatus Liberibacter asiaticus" and "Candidatus Liberibacter africanus") associated with citrus greening disease. Issue 5 (27th February 2020) - Ajene, Inusa Jacob; Khamis, Fathiya; van Asch, Barbara; Pietersen, Gerhard; Rasowo, Brenda Amondi; Ekesi, Sunday; Mohammed, Samira
Abstract: Aim: To quantify current and predict future distribution of the citrus greening pathogens "Candidatus Liberibacter asiaticus " (Las) in Africa and "Candidatus Liberibacter africanus " (Laf) globally. Location: Africa. Methods: Three species distribution models (MaxEnt, BIOCLIM and Boosted Regression Trees) were used to predict the current and future potential distribution of Las in Africa, and the potential global distribution of Laf, using long‐term bioclimatic variables. Two climate change scenarios (moderate and extreme) were employed to determine how future climate alterations may affect the potential distribution of Las in Africa. Presence data from global reports of Las, as well as the new positional points obtained in this survey, were used to predict the habitat suitability of the pathogen in Africa, while the presence data points of Laf were used to predict the global habitat suitability. Testing data comprised 25% of the presence only points. Results: Consensus of the three models predicted a potential distribution of Las in large areas of Western, Eastern and sub‐Saharan Africa. North Africa was mostly unsuitable for Las, except for the northern fringes. The potential distribution of Laf included South and Central America, Asia and Australia. In Europe, the United Kingdom and the Iberian Peninsula showed marginal suitability for Laf. The projections under the future climate change scenarios showed an increase in the Laf habitat suitability hotspots under the extreme scenario. Main conclusions: This study highlights the potential establishment and distribution in Africa of Las‐associated Huanglongbing and globally for Laf ‐ associated with African citrus greening disease. The ensemble modelling approach for the distribution of plant pathogens is a valuable tool for the development of strategies for crop protection. These results constitute an early alert for citrus‐producing regions that should inform strategies for surveillance and preventive management against the invasion and spread of this destructive disease.